The Effect of Product Quality and Service Quality on Consumer Satisfaction (Case Study Of Consumen Waroenk NewNormal) - Melda Yunita; Denny Rahmad Kardana (Penerbit ADM, 2023)
This study aims to determine the effect of product quality and service quality on consumer satisfaction in Waroenk New Normal consumers.This research uses a Quantitative approach. In this study used several data analysis techniques. Among them: Instrument test, classical assumption test, respondent challenge analysis, multiple linear regression analysis, Coeffesient determination, and hypothesis test. Based on the results of multiple linear regression analysis obtained the form of the regression equation Y = 2.165 + 0.00 (X1) + 0.041 (X2). From the results of research and hypotheses, it shows that the product quality of the t test results shows a value (sig a = 0.000 < 0.05) and t count 4.108 > value t table 1.99. The quality of service of the t test results shows a value (sig a = 0.041 < 0.05) and a calculated t value of 2.081 > a table t value of 1.991. Partially both product quality and Service Quality variables have a significant influence on purchasing decisions. From the results of research and hypotheses, it also shows that together Product Quality and Service Quality affect Consumer Satisfaction as seen from the results of the f test shows a sig value of a = 0.000 < 0.05 and a calculated f value of 30.801 > 3.11.